L’encadrement collégial : complexité et enjeux pour la professionnalisation de l’accompagnement doctoral - Nathalie Girard (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In a context of professionalization of doctoral training, doctoral supervision refers to a decompartmentalization of the doctoral student-supervisor pair. If team supervision has become an international standard and a common practice in France, the literature in the field remains focused on the dual relationship between a doctoral student and their supervisor. The objective of this article is to describe the diversity of organizational configurations of doctoral supervision teams. From a training system at INRAE, we have built a database on 76 theses, with the structural characteristics of the thesis and its support, but also the difficulties expressed by the PhD students and supervisors. The analysis of these data allows us to identify four types of doctoral supervision teams, beyond the pairs between a doctoral student and a supervisor. The organizational forms thus identified, sometimes classic, others more complex constituting multidisciplinary and/or multi-institutional teams around the doctoral student, sometimes extended to socio-economic actors, are described and confronted with the difficulties expressed by the stakeholders of these theses. The cross-sectional analysis of these results allows us to identify avenues for the training of doctoral students and supervisors, critical issues for the institutions that host these theses, but also research perspectives in the field of doctoral support.